ANALISIS KONSEP MAKIYAH-MADANIAH MUHAMMAD ABID AL-JABIRI TERHADAP OLIGARKI - Aziz Bashor Pratama (UIN Raden Mas Said Surakarta, 2023)
This paper examines the concept of makiyah-madaniah formulated by al-Jabiri in preparing his chronological interpretation. The model of interpretation based on historical analysis in the context of makiyah-madaniah tries to reveal the dialectics in the process of revelation and the Prophet's da'wah journey related to reality at that time. For al-Jabiri, this model can provide historical meaning not written in the text, so that the reality faced by the Prophet can be contextualized and developed in the present. The method used is descriptive analysis with the type of literature research. This article focuses on the problem of oligarchy by formulating the question of how the concept of makiyah-madaniah Abid al-Jabiri in analyzing the problem of oligarchy? The aim is to show that Islam is important in opposing and preventing oligarchic actions. As al-Jabiri shows that the makiyah verses deal with opposition and madaniah verses as a form of prevention in building state law. This article concludes that the Makiyah verses oppose tribal authority that hegemonizes other tribes and weak groups, resulting in social, economic, and political injustice. The madaniah verses are a form of the legal construction of property management and democracy to realize justice in the state and society.